2012
DOI: 10.2478/v10034-012-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of Oral-Facial-Digital Syndrome

Abstract: The oral-facial-digital (OFD) syndrome is a heterogeneous group of abnormalities that share anomalies of the oral cavity, face and digits of hands and feet. On the basis of other anomalies of brain, kidneys, limbs, eyes and other organs, at least 13 subgroups have been described. We here describe four unrelated patients with this syndrome, who have the typical facial, oral and digital anomalies and also anomalies of other organs and systems. Facial features, digital malformations, as well as the existence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Consistent with similar studies, additional malformations, including cleft palate, ptosis, squint, hypertelorism, diaphragmatic hernia, cerebral, cardiac, genital and skeletal abnormalities were also observed in our study (Aquino et al, 2015;Dellavia et al, 2011;Paradowska-Stolarz, 2014;Sukarova-Angelovska et al, 2014). A branchial fistula was found in one patient (pt 2), a finding that, to our knowledge was not reported before in WHS.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with similar studies, additional malformations, including cleft palate, ptosis, squint, hypertelorism, diaphragmatic hernia, cerebral, cardiac, genital and skeletal abnormalities were also observed in our study (Aquino et al, 2015;Dellavia et al, 2011;Paradowska-Stolarz, 2014;Sukarova-Angelovska et al, 2014). A branchial fistula was found in one patient (pt 2), a finding that, to our knowledge was not reported before in WHS.…”
Section: Discussionsupporting
confidence: 92%
“…Chromosome 5 is frequently involved in reciprocal translocations, together with chromosomes 22, 11, 4 and 9 [8]. As shown in our previous report [14], in this case we have proven translocation events on the short arm of chromosome 5. Translocation between chromosomes 5p and 17q as in the present case have been reported previously [15], although in their report there were additional features associated with trisomy 17q.…”
Section: Discussionsupporting
confidence: 82%
“…Of the various subtypes of OFDS, the most diverse genetic mutations have been identified in patients with OFD1. Frameshift, insertion, nonsense, missense, slicing, or genomic rearrangements of OFD1 gene have been reported in cases 2 11 12 . However, study reported that OFD1 gene mutation was found in 81 of 100 OFD1 patients (81.0%) who had undergone genetic testing 13 .…”
Section: Discussionmentioning
confidence: 99%